Mass Control and The Abuse of Technology in Ray Bradbury's Fahrenheit 451. (Raparin Journal of Humanities (RJH), 2023)
This article shows a kind of dystopian culture that controls citizens differently. Fahrenheit 451 is a genre which is possible to research and analyze; particularly the author attempts to ridicule society while simultaneously serving as a warning to the audience by illustrating what may happen to the world. It portrays an image of a totalitarian dystopia. Also, this novel was written by an author who was famous in the world and had a noble prize. On the other way, the abuse of technology is the other main issue in this paper, which is used for controlling people and spying on them.